2000
DOI: 10.1046/j.1523-1755.2000.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA topoisomerases in chronic proliferative kidney disease

Abstract: Topoisomerase IIalpha expression is tightly linked to cell cycling, and topoisomerase I is likely a reflection of gene transcription. Rapidly progressing glomerular disease therefore appears to be accompanied by active mesangial cell proliferation and increased metabolic activity in glomerular cells. The correlation with inflammatory infiltrates is likely to reflect a positive feedback mechanism involving cytokines, growth factors, and adhesion molecules. Assessment of topoisomerases may therefore be of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Such antigenic environment may allow the generation of anti-topoisomerase antibodies. On the other hand, these antibodies were proposed to act as positive feedback, augmenting antibody production and making their titer detectable in serum [21,22]. Anti-Scl 70 antibodies probably do not play a role in the pathogenesis of kidney damage, because no difference in the frequency of kidney involvement has been found between scleroderma patients who have or lack this antibody [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such antigenic environment may allow the generation of anti-topoisomerase antibodies. On the other hand, these antibodies were proposed to act as positive feedback, augmenting antibody production and making their titer detectable in serum [21,22]. Anti-Scl 70 antibodies probably do not play a role in the pathogenesis of kidney damage, because no difference in the frequency of kidney involvement has been found between scleroderma patients who have or lack this antibody [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of topoisomerase I overexpression in RPGN, such us lupus nephritis and RPGN (including anti-GBM disease). The use of topoisomerase I inhibitors in such cases has been proposed, because of the potential progression-reducing effect of these drugs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of TopoIIa is predominant in actively proliferating cells and has been reported in non-neoplastic kidney lesions and several malignancies, including breast, colon and pancreatic cancer, and meningiomas. [10][11][12][13][14] TopoIIa inhibitors, antibiotics actinomycin D and anthracycline doxorubicin, along with vincristine, are used as the main chemotherapeutic agents for the treatment of Wilms' tumour. 6 7 It was suggested that TopoIIa gene copy numbers and enzyme expression may correlate with the efficacy of anthracycline treatment in breast cancer.…”
mentioning
confidence: 99%